Stress Levels and Hormonal Coupling and Their Relationship with Sports Performance in an Elite Women’s Volleyball Team - Álvaro Miguel-Ortega; Julen Fernández-Landa; Julio Calleja-González; Juan Mielgo-Ayuso (Applied Sciences, 2023)
The testosterone–cortisol ratio is a concept in human biology that refers to the balance between testosterone, the main anabolic steroid, and cortisol, another steroid hormone. The two hormones are said to be habitually positively “coupled”. Increases or decreases in testosterone tend to be associated with corresponding increases or decreases in cortisol, and vice versa. The present study explored hormone coupling and its relationship to stress levels in the sport performances of an elite women’s volleyball team. (1) Aim: to assess the testosterone–cortisol concentration dynamic over 16 weeks and its link to sport performance in elite female volleyball players (height: 1.8 ± 0.1 m; 24.2 ± 2.7 years; playing experience 15 ± 2.8 years; years played at elite level 4.2 ± 2.2; testosterone–cortisol index time 1: 3.9 vs. time 2: 4.3) (n = 11). (2) Methods: blood samples (hormones among other biochemical parameters) and sports performance measurements (aerobic and anaerobic power among other tests) were taken from members of an elite women’s volleyball team over 16 weeks of competition. (3) Results: female volleyball players showed patterns of hormonal change and adaptation to stress. (4) Conclusions: the current investigation demonstrated that elite female volleyball players have higher basal levels of testosterone and cortisol than normal healthy women. The impact of training and competition is clearly reflected in the levels of T. Cortisol levels increase at the beginning of training and remain elevated throughout the season, but without significant changes.